KEANEKARAGAMAN JENIS FAMILI URTICACEAE DI HUTAN DESA BUKUM KECAMATAN SIBOLANGIT KABUPATEN DELI SERDANG SUMATERA UTARA - Ramayati, Ike; Hutasuhut, Melfa Aisyah; Idami, Zahratul (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
The Urticaceae family is herbaceous, semi-shrub, climbing (liana), small trees, and shrubs that have important ecological and economic roles. This research was conducted to determine the composition and structure, diversity, and utilization of Urticaceae family plants in the Forest of Bukum Village, Sibolangit District, Deli Serdang Regency, North Sumatra. This research is an exploratory survey using the quadratic method. The plots were purposive sampling as many as 10 plots measuring 10m x 10m. There are 25 species of plants in the Urticaceae family with 547 individuals. The most common type of plant found is Elatostema sessile JRForst. & G. Forst. Highest importance index on Elatostema sessile JRForst. & G. Forst. (INP 91,30%). The plant diversity index of the Urticaceae family is moderate with H' 2.64 which is included in the stable community.